Heidi Heckelbeck takes the cake - Coven, Wanda (Coven, Wanda. Heidi Heckelbeck, 2020)
When Heidi's busy life keeps her from remembering her friend Bruce's birthday, she decides to throw a magical make-up party to apologize.